Development of a Feeder Port of Tanjung Ringgit Facilities to Support Implementation of Sea Tollway - Windra Priatna Humang; Rakhmawati Natsir; Amiruddin Akbar Fisu (Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2021)
Improvement of connectivity between islands known as the sea Tollway initiative has minimized pricing inequalities and improved connection in poor, remote, outer, and border areas. The biggest challenge to implementing the Program of Sea Tollway are port infrastructure readiness, collector and feeder ports for the movement of goods into a node. Tanjung Ringgit Port must serve as a feeder port for Makassar's main port to support the program. The approach used in this research is quantitative. Data collection consists of primary data through interviews, field observations and secondary data. This research used port performance analysis to analyze the needs of port performance facilities such as container field facilities, warehouses and jetty, and SWOT analysis to determine port development policies and strategies. The findings of the study show that more warehouse space will be required until 2035. The development strategy of port capacity and facilities is done by changing patterns of shipments, a dedicated terminal for large volume cargo, infrastructure development, equipment and container stevedoring, warehouse replacement truck losing systems.